Entre o local e o nacional: debate sobre a difusão da renda básica universal no Brasil e o papel de Maricá - Martins, Paulo Sodré (2025)
In a context of structural inequality and increasing labor precarization, Brazil presents a unique setting to analyze the feasibility of Universal Basic Income (UBI) policies, particularly in light of its well-established experience with large-scale cash transfer programs. This article explores the debates surrounding the diffusion pathways of UBI in the country, focusing on dynamics driven, on one hand, by the “Maricá Model” and, on the other, by federal policies, especially the Bolsa Família Program (PBF). It examines how these cases appear within different perspectives of the debate. To that end, a shared vocabulary grounded in the literature on Policy Transfer, Diffusion, and Circulation is proposed to frame the different viewpoints involved. The analysis is illustrated through qualitative interviews, literature review, and document analysis, incorporating contributions from the political sphere, international academia, and practitioners directly involved in the implementation of the “Maricá model.” In doing so, the article offers an overview of the challenges and opportunities for the diffusion of a UBI policy in Brazil